A inter-relação da oferta de água, sombra no comportamento ingestivo de bovinos leiteiros em pastejo - Souza, Edenilson Robson (2017)
Milk production from family farms in the south-west of Paraná stands out in the national scenario for the productive indexes. The silvipastoral system unifies the agricultural and cattle production, optimizing the production by cultivated area and promotes the thermal comfort to the animals. The objective of this research was to evaluate the interrelation between water supply and shade in the ingestive behavior of dairy cows in different pasture milk production systems. The experiment was developed at the Federal Technological University of Paraná - UTFPR - Campus Dois Vizinhos, between November 2016 and April 2017. The experimental area was 0.5 ha, subdivided into 12 paddocks of approximately 200 m², pasture Was composed of African star grass (Cynodon nlemfuensis) and Aruana grass (Panicum maximum Jacq.). The experiment was composed of four (4) treatments and (3) three replicates each: silvipastoral system (with shade), with water supply at the picket; Silvipastoral system (with shade), supply of water in the corridor; Conventional system (no shade), picket water; Conventional system (no shade) water in the hallway. The water supply was by means of a drinking fountain with capacity of 100 liters of water, with one (1) meter of diameter per picket line. Twelve animals distributed in the treatments were used. The observation of the animals in the pickets was carried out in three evaluations by a group of trained observers, subdivided into pairs, during three (3) consecutive days, totaling 180 hours of behavioral evaluation. The data collected were subjected to analysis of variance and regression at 5% probability using the SAS statistical program. The means of the treatments were compared by the Tukey test with a significance of 5% of error probability. The average temperature and humidity index (ITU) of 69, animals of the conventional system presented higher rectal temperature (TR) than those of silvipastoral system. In both systems evaluated the animals had physiological patterns altered with increasing ambient temperature. Physiological changes were concomitant with behavioral changes in animals. The animals kept in the silvopastoral system grazed more than the animals of the conventional system. Animals in the silvopastoral system ruminated more lying down than animals in the conventional system. The animals in the silvipastoral remained less time in standing idle than the conventional ones. Cows kept in the silvipastoral system ingested more water than the cows that were in the conventional system. The animals that had the nearest water point (inside the picket) ate more water than the animals that had the water point in the corridor. It is concluded that the silvopastoral system is more adequate than the conventional system for raising dairy cattle to pasture, and that the presence of shade and water in the pickets are indispensable conditions for animal welfare.